If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 141 = 5x + -3 Reorder the terms: 141 + 6x = 5x + -3 Reorder the terms: 141 + 6x = -3 + 5x Solving 141 + 6x = -3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 141 + 6x + -5x = -3 + 5x + -5x Combine like terms: 6x + -5x = 1x 141 + 1x = -3 + 5x + -5x Combine like terms: 5x + -5x = 0 141 + 1x = -3 + 0 141 + 1x = -3 Add '-141' to each side of the equation. 141 + -141 + 1x = -3 + -141 Combine like terms: 141 + -141 = 0 0 + 1x = -3 + -141 1x = -3 + -141 Combine like terms: -3 + -141 = -144 1x = -144 Divide each side by '1'. x = -144 Simplifying x = -144
| XY+Y= | | -13+13=0 | | 5x-2(4+4x)=11 | | -4(4+7n)+5(3+4n)=-5n-2n | | a^4-7a^2+10=0 | | 9x-8=3x+4 | | 165+20x=180 | | -6n=2m+3 | | -4(4+7n)+5(3+4n)=-5-2n | | 15v-9v=42 | | y=-2(5)+2 | | x+2x+[x+3]=23 | | y-11=-27 | | 17x-10x=-6 | | 10z-6=4z-15-3z | | 15+20x=180 | | 140795*100/145= | | 6X+1+.05=252 | | 4x+10y=100 | | a^2-7a^2+10=0 | | 10y+10=90 | | 16(2x-8)=4(8x+9) | | 3b-(13)+4b=7b+1 | | -20=-5+3(y-5) | | 0.75a=0.5625 | | 2[3-(2a+7)]-2=6(6-a) | | 8x-2=13x+12.25 | | -6x-7=-2(3x+5) | | 4(z/2+3)=16+3z | | 108=-32t-22 | | 23-k=-3(5k-3) | | 10x^2+96=0 |